ANALISIS AWAL PEMBELAJARAN IPAS DI KELAS IV: KEBUTUHAN MEDIA PEMBELAJARAN YANG KONTEKSTUAL DAN MENYENANGKAN - Hafidza, Hikmah; Juita Harun, Gustiayu; Yufriana Devi, Meila (Cerdas Proklamator, 2025)
Learning Natural and Social Sciences (IPAS) in elementary schools faces various challenges, including difficult-to-understand material, a dense curriculum, and limited learning media. This study aims to analyze the needs of teachers and students and develop effective game-based learning media to improve understanding and learning motivation. The research method used a quantitative descriptive approach with data collection techniques through a closed-ended questionnaire administered to teachers and fourth-grade students. Data were analyzed quantitatively by calculating the percentage of responses and qualitatively to obtain an in-depth picture of learning needs. The results showed that all teachers (100%) agreed that the IPAS material was difficult to understand and too dense, while all students (100%) admitted to never using learning media during the learning process. On the other hand, all respondents (teachers and students) stated that game-based media was the right solution because it was considered suitable for student characteristics and able to increase learning motivation. The conclusion of this study confirms that the development of game-based IPAS learning media with a microlearning approach and gamification elements can be an innovative solution to overcome learning challenges. These findings recommend the importance of teacher training in digital media development and the integration of educational games in the IPAS curriculum.